2017
DOI: 10.1097/meg.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sleep architecture parameters in cirrhotic patients with recurrent hepatic encephalopathy with the use of rifaximin

Abstract: Patients with recurrent HE suffer from poor sleep quality and excessive daytime sleepiness. On 24-h PSG, rifaximin improves objective sleep architecture parameters with no changes in the subjective quality of sleep and sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“… 2 , 12 , 25 , 27 29 PSG has also been performed, confirming the presence of short TST, decreased sleep effi-ciency (SE), frequent awakenings, and lower amounts of slow wave sleep (SWS) and rapid eye movement (REM) sleep in cirrhotic patients. 7 , 28 , 33 Animal studies in cirrhotic rat models have corroborated these findings. 34 Interestingly, when we performed 24h-PSG, we were able to show that the amount of objective sleep over 24 hours is much more important than nighttime sleep (575 vs 471 minutes), since a number of naps are recorded in this population ( Figure 1 ).…”
Section: Characteristics and Prevalence Of Sleep Disturbances In Livementioning
confidence: 75%
See 4 more Smart Citations
“… 2 , 12 , 25 , 27 29 PSG has also been performed, confirming the presence of short TST, decreased sleep effi-ciency (SE), frequent awakenings, and lower amounts of slow wave sleep (SWS) and rapid eye movement (REM) sleep in cirrhotic patients. 7 , 28 , 33 Animal studies in cirrhotic rat models have corroborated these findings. 34 Interestingly, when we performed 24h-PSG, we were able to show that the amount of objective sleep over 24 hours is much more important than nighttime sleep (575 vs 471 minutes), since a number of naps are recorded in this population ( Figure 1 ).…”
Section: Characteristics and Prevalence Of Sleep Disturbances In Livementioning
confidence: 75%
“… 13 However, another study, which assessed sleep by PSG, reported parallel improvements in sleep quality and HE. 28 In an animal model of HE in rats, Felipo et al showed that HE rats had more awakenings during sleep and more naps during active phase than controls, 40 supporting the association between sleep disturbances and HE. In another study, high levels of interleukin-6, and not the presence of HE, were associated with poor sleep, measured by PSQI.…”
Section: Pathophysiological Mechanisms Of Sleep Disturbances In Livermentioning
confidence: 97%
See 3 more Smart Citations